Os condicionantes do teletrabalho potencial no Brasil - Geraldo Sandoval Góes; Felipe dos Santos Martins; Vinícius de Oliveira Alves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This Discussion Paper aims to analyze the constraints linked to the individual characteristics of the worker, such as gender, race or color, education and age group, as well as characteristics of the labor market, such as, type of employment relationship and sector of economic activity, related to home office. For this, data from the Pesquisa Nacional por Amostra de Domicílios Contínua (PNAD Contínua), from the Brazilian Institute of Geography and Statistics (IBGE), in Brazil and macro-regions and linear and logit models are used. The results suggest a specific worker profile for which work from home would be more feasible. In fact, white people, women, with a university degree, working in the formal sector and in the public sector are those employed with the highest estimated chance of being in this labor regime. Another highlight is at the spatial level, in which it is found that, once the set of conditions is controlled, with the exception of the Southeast, there are no statistically significant differences between the North region and the others in the estimated chance of potentially acting at work remote.
10419/284886
Keywords: J21; J22; J01; 330; home office; remote work; labor sector; labor economics